Reliability Analysis of Silsafe4000 Railway Signaling Equipment at Labakkang Station, Pangkajene and Kepulauan - Asmawaty Azis; Mohamad Lukman Hakim; Kurniawan Harun Rasyid (Jurusan Pendidikan Teknik Elektro, 2025)
The SILSafe4000 electrical signaling system was implemented at the Labakkang Station on the Makassar-Parepare railway line as part of a newly developed operational corridor. This study aimed to assess the reliability and safety performance of SILSafe4000 using a quantitative analytical approach, combining technical performance standard matching and operational capacity evaluation. Field data will be obtained through direct observation, measurement of key technical parameters, and analysis of operational records from April to September 2025. The results indicate that the system generally operates within acceptable performance thresholds and is capable of supporting up to 52 train movements per day compared with the actual six daily operations. Deviations were identified in the grounding resistances and detection voltages of certain devices, which may affect long-term reliability if not corrected. This study proposes targeted technical improvements, including ground relocation, voltage stabilization, and detection circuit adjustments. This study is limited to a short-term technical evaluation of a low-density rail corridor and does not account for environmental variability, human factors, or long-term reliability indicators. The findings provide practical recommendations for reliability enhancement and can serve as a reference for signaling system optimization in the early operational stages of new railway networks. Overall, the SILSafe4000 system is considered reliable for current operational use, with the need for proactive maintenance and continuous performance monitoring to ensure its reliability.